Use of Social Media to Improve Religious Moderation Among Youth - Yunarti, Susi; Harmaningsih, Dian; Wijayanti, Wijayanti (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Indonesia consists of various tribes that have cultural, racial and religious diversity. The diversity of the Indonesian nation has proven to be a strong foundation for development. Social media has proven to be a powerful tool in various social movements. Social media also has the potential to be a driver of paradigm change. Fahrudin Faiz's YouTube content which contains life and religious motivation can be used as an alternative solution.The purpose of this research is to determine the use of social media to increase audience religious moderation. The theory used is the Elaboration Likelihood Model, explaining how a message can change attitudes (or produce resistance to change) by making someone think hard about the points made (using central processing). This research uses the case study method of Fahrudin Faiz's YouTube content. Data was collected through interviews with UPI YAI Jakarta students. The research results showed that the informants after watching Fahrudin Faiz's YouTube content gained additional insight into religious moderation and motivation which was useful when they had to face problems in their lives.